Increased risk of hospitalization for acute hepatitis in patients with previous exposure to NSAIDs - Lee, Chang-Hsing; Wang, Jung-Der; Chen, Pau-Chung (Pharmacoepidemiology and drug safety, 2010)
Background Epidemiological studies related to hospitalization due to the hepatotoxicity of traditional non‐steroidal anti‐inflammatory drugs (NSAIDs) are infrequent, and case reports of hepatotoxicity of nimesulide, celecoxib, and rofecoxib seem to be increasing. The reimbursement database of National Health Insurance (NHI) in Taiwan provided an opportunity for post‐marketing surveillance. We conducted this study to determine the association between the use of hepatoxic NSAIDs and increased hospitalizations related to acute hepatitis. Methods We included hospitalized subjects with a major diagnosis of acute or sub‐acute necrosis of liver or toxic hepatitis and excluded viral and other causes of hepatobiliary diseases from the NHI database from 1 April 2001 to 31 December 2004. We applied two kinds of models to analyze by uni‐directional and bi‐directional case‐crossover designs during the 28 days exposure periods and performed conditional logistic regression models. Results There were 4519 cases of hospitalization relating to acute hepatitis, and the odds ratios of celecoxib, nimesulide, dicofenac, ibuprofen, and other hepatoxic NSAIDs were significantly increased. Compared with the adjusted odds ratios of other hepatoxic NSAIDs (OR = 2.13, 95%CI = 2.00, 2.28), celecoxib (OR =1.92, 95%CI = 1.38, 2.69) was similar during the 28 days by our uni‐directional case‐crossover design. Conclusions Our results provide evidence for an increased risk of hospitalization with acute hepatitis among hepatoxic NSAIDs including celecoxib users. Further mechanistic research is warranted in order to document celecoxib's hepatotoxicity. Copyright © 2010 John Wiley & Sons, Ltd.